FAVLAB II: Digital fabrication in Favela da Maré, Rio de Janeiro - Natividade, V.; Cardoso, A. (SIGraDi 2020 Transformative Design - XXIV International Conference of the Iberoamerican Society of Digital Graphics, 2020)
This article presents and discusses the result of a digital fabrication laboratory in a favela in Rio de Janeiro, Brazil. The laboratory is an experimental studio dedicated to teaching design and sharing technological knowledge between architecture students and young slum dwellers. The laboratory aims to explore collaborative design solutions for the public space in informal contexts, which meets local demands and presents an innovative and inclusive approach to digital design and fabrication. The paper offers a comprehensive theoretical background and the detailed methodology used in the studio.